Foam-gelcasting preparation, microstructure and thermal insulation performance of porous diatomite ceramics with hierarchical pore structures. Issue 7 (July 2017) - Han, Lei; Li, Faliang; Deng, Xiangong; Wang, Junkai; Zhang, Haijun; Zhang, Shaowei
Graphical abstract: Abstract: Hierarchically pore-structured porous diatomite ceramics containing 82.9∼84.5% porosity were successfully prepared for the first time via foam-gelcasting using diatomite powder as the main raw material. Sizes of mesopores derived from the raw material and macropores formed mainly from foaming were 0.02∼0.1 μm and 109.7∼130.5 μm, respectively. The effect of sintering temperature, additive content and solid loading of slurry on pore size and distribution, and mechanical and thermal properties of as-prepared porous ceramics were investigated. Compressive strength of as-prepared porous ceramics increased with sintering temperature, and the one containing 82.9% porosity showed the highest compressive strength of 2.1 ± 0.14 MPa. In addition, the one containing 84.5% porosity and having compressive strength of 1.1 ± 0.07 MPa showed the lowest thermal conductivity of 0.097 ± 0.001 W/(m·K) at a test temperature of 200 ̊C, suggesting that as-prepared porous ceramics could be potentially used as good thermal insulation materials.